The impacts of food inflation on poverty in Malaysia / Nor Azira Ismail, Shahiszan Ismail and Jamilah Laidin - Ismail, Nor Azira; Ismail, Shahiszan; Laidin, Jamilah (Universiti Teknologi MARA, Kedah, 2022)
Based on a report from the Department of Statistics Malaysia (DSM) released on 21, January 2022, Malaysia’s inflation, which was measured by the Consumer Price Index (CPI), increased by 3.4 percent in June 2022, from a year earlier. This was driven by a 6.1 percent rise in food prices, which remained the main contributor to the rise in inflation. Moreover, the inflation was also contributed by the increase in the index of transport (5.4 percent), furnishing, household equipment, and routine household maintenance (3.4 percent), and housing, water, electricity, gas, and other fuels (2.2 percent). The issues of food inflation arise from various factors, such as sharp spikes in global commodities prices causing fluctuations in international terms of trade, rise in the price of animal feedstuff, as well as the closure of the national border due to the Movement Control Orders (MCOs) during the pandemic. All these have influenced the fluctuation of prices in the local market. This paper identified three impacts of food inflation in Malaysia as follows.